Skip Furrow Irrigation Increases Water Productivity, Maintains Yield and Decreases Soil Salinity for Sunflower in the Coastal Zone of the Ganges Delta - Khokan Kumer Sarker; Mohammed Mainuddin; Richard W. Bell; Manoj Kumar Nanda; Md. Mainul Islam; Md. Abdul Quddus; Mahanambroto Das; Md. Anower Hossain (Irrigation and Drainage, 2026)
Water‐saving irrigation is essential for crops in saline regions where freshwater resources are scarce. We tested furrow irrigation methods and planting techniques in terms of yield, water savings, water productivity (WP), soil salinity (EC e ) and soil water content (SWC) for sunflower in saline soils. Planting on the top of the ridge (T) or side slope on the ridge (S) were tested in factorial combination with (i) skip fixed furrow irrigation (SFFI), (ii) alternate furrow irrigation (AFI) or (iii) every furrow irrigation (EFI). The sunflower yield was significantly greater with the side of the ridge planting than on the top of the ridge. In consecutive years, sunflower yields were not significantly different among the furrow irrigation combinations with planting on side slopes of ridges. However, compared with the EFI, the SFFI and AFI saved 25 28% of the irrigation water and improved the WP. At a soil depth of 30 cm, the SFFI and AFI had significantly lower EC e values than did the EFI. Both skip furrow methods, with side slope planting on the ridge, offer water savings without sacrificing yields while decreasing the soil salinity and increasing the WP of sunflower in the water‐scarce, saline coastal regions of the Ganges Delta.

A cross-sectional view of the drinking water scenario in a climate-stressed setting: Case study from southwestern Bangladesh - Tasneem Chowdhury Fahim; Md Mainul Islam; Zinat Hasiba; Md. Ahasanul Hoque (Utilities Policy, 2026)

Ghrelin-disrupting activity of arsenic and its relation to cardiometabolic diseases - Kamrun Nahar Rossi; Faysal Abedin; Nayan Chandra Mohanto; Biplob Ahmed; Sobuj Mia; Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; Ahsanul Mahbub Jubayar; et al. (Toxicology and Applied Pharmacology, 2026)

Association between Arsenic Exposure and CCL5: its Implications in Asthma and Skin Lesions - Osman Goni; Nesar Uddin; Rajoana Karim Rimi; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Sharon Jahan Sarder; Junayed Sadi; Mainul Islam; Victor Mondal; K M Ahsanul Kabir; Abu Eabrahim Siddique; et al. (Exposure and Health, 2026)

Relationship of fractalkine with arsenic exposure and the risk of cardiovascular diseases - Nesar Uddin; Rajoana Karim Rimi; Osman Goni; Nayan Chandra Mohanto; Kamrun Nahar Rossi; Faysal Abedin; Sharmin Akter Beauty; Biplob Ahmed; Sobuj Mia; Sharon Jahan Sarder; Sajib Hossain; Mainul Islam; et al. (Environmental Toxicology and Pharmacology, 2025)

Retraction notice to “Personal protective equipment-derived pollution during Covid-19 era: A critical review of ecotoxicology impacts, intervention strategies, and future challenges” [Sci. Total Environ. 887(2023) 164164] - Mehedi Hasan; Abu Reza Md. Towfiqul Islam; Most. Mastura Munia Farjana Jion; Md. Naimur Rahman; Susmita Datta Peu; Arnob Das; A.B.M. Mainul Bari; Md Saiful Islam; Subodh Chandra Pal; Aznarul Islam; Tasrina Rabia Choudhury; Md Refat Jahan Rakib; et al. (Science of The Total Environment, 2025)

Optimizing coastal groundwater quality predictions: A novel data mining framework with cross-validation, bootstrapping, and entropy analysis - Abu Reza Md Towfiqul Islam; Md. Abdullah-Al Mamun; Mehedi Hasan; Mst. Nazneen Aktar; Md Nashir Uddin; Md. Abu Bakar Siddique; Mohaiminul Haider Chowdhury; Md. Saiful Islam; A.B.M. Mainul Bari; Abubakr M. Idris; Venkatramanan Senapathi (Journal of Contaminant Hydrology, 2025)

Land use land cover dynamics and its impact on SWL fluctuation in shallow alluvial aquifers of the Purba Bardhaman plain, West Bengal, India - Mainul Islam; Arijit Majumder (Environment, Development and Sustainability, 2025)

Retraction notice to “Managing the invisible threat of microplastics in marine ecosystems: Lessons from coast of the Bay of Bengal” [Sci. Total Environ. 889 (2023) 164224] - Al-Nure Mubin; Shahoriar Arefin; Md. Sonir Mia; Abu Reza Md. Towfiqul Islam; A.B.M. Mainul Bari; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; M. Safiur Rahman; Venkatramanan Senapathi; Abubakr M. Idris; Guilherme Malafaia (Science of The Total Environment, 2024)

Predicting groundwater phosphate levels in coastal multi-aquifers: A geostatistical and data-driven approach - Md. Abdullah-Al Mamun; Abu Reza Md Towfiqul Islam; Mst. Nazneen Aktar; Md Nashir Uddin; Md. Saiful Islam; Subodh Chandra Pal; Aznarul Islam; A.B.M. Mainul Bari; Abubakr M. Idris; Venkatramanan Senapathi (Science of The Total Environment, 2024)

Assessment of heavy metals and proximate composition in jellyfish (Lobonemoides robustus Stiasny, 1920) collected from Cox's Bazar coast: Human health risk assessment - Md. Simul Bhuyan; Md. Tarikul Islam; Sayeed Mahmood Belal Haider; Lamia Yacoubi; Mala Khan; Mir Mohammad Ali; Debasish Pandit; Md. Mainul Huda; Sheuly Akter; Md. Raisul Islam Rabbi; Nayan Kumer Kundu; Md. Mehedi Hasan; et al. (Marine Pollution Bulletin, 2024)

A new approach from public behavioral attitudes and perceptions towards microplastics: Influencing factors, and policy proposals - Abdulla Al Masud; Abu Reza Md Towfiqul Islam; Abdullah Al Mamun; G.M. Monirul Alam; Alireza Arabameri; A.B.M. Mainul Bari; Subodh Chandra Pal; Md Refat Jahan Rakib; Venkatramanan Senapathi; Md Bodrud-Doza; Abubakr M. Idris; Guilherme Malafaia (Ocean & Coastal Management, 2024)

A data driven approach to assess the petrophysical parametric sensitivity for lithology identification based on ensemble learning - Md. Ashiqul Islam Shuvo; Syed Mainul Hossain Joy (Journal of Applied Geophysics, 2024)

An integrated coastal ecosystem monitoring strategy: Pilot case in Naf-Saint Martin Peninsula, Bangladesh - Subrata Sarker; Lilian A. Krug; Kazi Mainul Islam; Shyamal Chandra Basak; A.N.M. Samiul Huda; Md. Shahadat Hossain; Nabanita Das; Shashowti Chowdhury Riya; Eurida Liyana; Gawsia Wahidunnessa Chowdhury (Science of The Total Environment, 2024)

A review of microplastic threat mitigation in Asian lentic environments - Moriom Rahman Sadia; Mehedi Hasan; Abu Reza Md. Towfiqul Islam; Most. Mastura Munia Farjana Jion; Md Abdullah Al Masud; Md. Naimur Rahman; Susmita Datta Peu; Arnob Das; A.B.M. Mainul Bari; Md. Saiful Islam; Subodh Chandra Pal; Md. Refat Jahan Rakib; et al. (Journal of Contaminant Hydrology, 2024)

Fuzzy logic, geostatistics, and multiple linear models to evaluate irrigation metrics and their influencing factors in a drought-prone agricultural region - S.M. Rabbi Al Zihad; Abu Reza Md Towfiqul Islam; Md Abu Bakar Siddique; Md Yousuf Mia; Md Saiful Islam; Md Aminul Islam; A.B.M. Mainul Bari; Md Bodrud-Doza; Sobhy M. Yakout; Venkatramanan Senapathi; Sumanta Chatterjee (Environmental Research, 2023)

RETRACTED: Managing the invisible threat of microplastics in marine ecosystems: Lessons from coast of the Bay of Bengal - Al-Nure Mubin; Shahoriar Arefin; Md. Sonir Mia; Abu Reza Md. Towfiqul Islam; A.B.M. Mainul Bari; Md. Saiful Islam; Mir Mohammad Ali; Md. Abu Bakar Siddique; M. Safiur Rahman; Venkatramanan Senapathi; Abubakr M. Idris; Guilherme Malafaia (Science of The Total Environment, 2023)

RETRACTED: Personal protective equipment-derived pollution during Covid-19 era: A critical review of ecotoxicology impacts, intervention strategies, and future challenges - Mehedi Hasan; Abu Reza Md. Towfiqul Islam; Most. Mastura Munia Farjana Jion; Md. Naimur Rahman; Susmita Datta Peu; Arnob Das; A.B.M. Mainul Bari; Md. Saiful Islam; Subodh Chandra Pal; Aznarul Islam; Tasrina Rabia Choudhury; Md. Refat Jahan Rakib; et al. (Science of The Total Environment, 2023)

Can an annual flood induce changes in channel geomorphology? - Aznarul Islam; Biplab Sarkar; Ujwal Deep Saha; Mainul Islam; Susmita Ghosh (Natural Hazards, 2022)

Genetic diversity and yield performance among T. Aman rice (Oryza sativa L.) landraces in Barishal region of Bangladesh - Shamim Mia; Nasar Uddin Ahmed; Mohammad Zahidul Islam; Md. Mainul Islam Rashad; Md. Monirul Islam; A. K. M. Mostafa Zaman (Journal of Crop Science and Biotechnology, 2022)

Pattern analysis of trace gases over Bangladesh using satellite remote sensing - Md Monirul Islam; Md Mainul Islam Mamun; Ahsan Habib Rasel; Mumnunul Keramat (International Journal of Remote Sensing, 2015)